Distal pancreatectomy: extent of resection determines surgical risk categories - Loos, Martin; Mack, Claudia; Xu, An Ting L.; Hassenpflug, Matthias; Hinz, Ulf; Mehrabi, Arianeb; Berchtold, Christoph; Schneider, Martin; Saeedi, Mohammed al; Roth, Susanne; Hackert, Thilo; Büchler, Markus W. (Annals of surgery, 2024)
Background: - Recently, subclassification of pancreatoduodenectomy in 4 differing types has been reported, because additional major vascular and multivisceral resections have been shown to be associated with an increased risk of postoperative morbidity and mortality. - Objective: - To classify distal pancreatectomy (DP) based on the extent of resection and technical difficulty and to evaluate postoperative outcomes with regards to this classification system. - Methods: - All consecutive patients who had undergone DP between 2001 and 2020 in a high-volume pancreatic surgery center were included in this study. DPs were subclassified into 4 distinct categories reflecting the extent of resection and technical difficulty, including standard DP (type 1), DP with venous (type 2), multivisceral (type 3), or arterial resection (type 4). Patient characteristics, perioperative data, and postoperative outcomes were analyzed and compared among the 4 groups. - Results: - A total of 2135 patients underwent DP. Standard DP was the most frequently performed procedure (64.8%). The overall 90-day mortality rate was 1.6%. Morbidity rates were higher in patients with additional vascular or multivisceral resections, and 90-day mortality gradually increased with the extent of resection from standard DP to DP with arterial resection (type 1: 0.7%; type 2: 1.3%; type 3: 3%; type 4: 8.7%; P<0.0001). Multivariable analysis confirmed the type of DP as an independent risk factor for 90-day mortality. - Conclusions: - Postoperative outcomes after DP depend on the extent of resection and correlate with the type of DP. The implementation of the 4-type classification system allows standardized reporting of surgical outcomes after DP improving comparability of future studies.
Gesehen am 07.06.2024